PROMOTING INVESTMENT ACTIVITY OF LARGE TAXPAYERS THROUGH TAX INCENTIVES (American Journal of Business Management, Economics and Banking, 2023)
The article is devoted to consideration of the efficient ways to promote investment activity of large taxpayers in our country. In addition, the article reveals the economic significance of the “tax incentive” concept. Relevant conclusions have been developed based on the analytical data on the tax incentives applied in our country by types of taxes.